Preparation method of high-strength carbon-coated aluminum foil current collector for lithium battery

CN118016897BActive Publication Date: 2026-10-30JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410173300.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2026-10-30
Estimated Expiration
2044-02-07

AI Technical Summary

Benefits of technology

[0027](1)本发明通过对粘结剂的改性,改善涂层结构,提高了浆料的内聚力以及与铝箔表面的接触,从而在高低温下能够有效应对锂离子的脱嵌和嵌入导致的体积变化,保证电极材料在充放电过程中的稳定性。本发明还使用纳米涂敷技术在铝箔表面进行单面双层异构涂敷,在保证铝箔表面粘结型的同时,提供了大量的接触位点,使得极片涂敷过程中能够与箔材结合更为紧密,增加了极片剥离强度,改善了容量保持率,进而改善电池的使用性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of carbon-coated current collector, in particular to a preparation method of high-strength carbon-coated aluminum foil current collector for lithium battery, the present application improves the cohesion of the slurry and the contact with the surface of the aluminum foil by modifying the binder and improving the coating structure, thereby effectively coping with the volume change caused by the deintercalation and intercalation of lithium ions at high and low temperatures, ensuring the stability of the electrode material during the charging and discharging process. The present application also uses nano-coating technology to perform single-sided double-layer heterogeneous coating on the surface of the aluminum foil, while ensuring the adhesion type of the aluminum foil surface, providing a large number of contact sites, so that the pole piece coating process can be combined more closely with the foil, increasing the pole piece peeling strength, improving the capacity retention rate, and further improving the performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon-coated current collector technology, specifically a method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries. Background Technology

[0002] Lithium-ion batteries are widely used in many fields such as automobiles and mobile phones due to their high energy density. The main components of a lithium battery include positive and negative electrode active materials, electrolyte, separator, and positive and negative electrode current collectors. Currently, aluminum foil, copper foil, composite aluminum foil, composite copper foil, and carbon-coated aluminum foil, carbon-coated copper foil, composite carbon-coated aluminum foil, and composite carbon-coated copper foil with improved surfaces are the main materials used to transport electrons. However, traditional aluminum foil or copper foil current collectors have the problem of high interfacial resistance, while carbon-coated current collectors can improve interfacial resistance and improve battery charging and discharging. Existing carbon coatings can effectively improve the charge and discharge capacity retention rate under normal charge and discharge conditions, but there will be significant capacity differences in different usage environments. The carbon-coated current collector of this invention can improve the capacity uniformity of the battery during charge and discharge at high and low temperatures. By increasing the surface roughness of the carbon-coated current collector and improving the coating structure, the stability of the adhesion between the coating and the electrode is ensured, thus guaranteeing the capacity retention rate under extreme environments.

[0003] To address the aforementioned issues and improve the capacity retention of current collectors under high and low temperature environments, this invention provides a method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries, so as to solve the problems mentioned in the background art.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0006] A method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries includes the following steps:

[0007] Step 1: Take the adhesive, deionized water, conductive agent, and curing agent, stir them evenly to obtain the lower coating slurry;

[0008] Step 2: Apply the lower coating slurry to one side of the aluminum foil and bake at 70-130℃ for 20s-3min to obtain the carbon-coated aluminum foil current collector semi-finished product;

[0009] Step 3: Take the adhesive, deionized water, conductive agent, and curing agent, stir them evenly to prepare the top coating slurry;

[0010] Step 4: Apply the top coating slurry to the side of the carbon-coated aluminum foil current collector semi-finished product that has the bottom coating slurry, and bake it at 70-130℃ for 20s-3min to obtain the carbon-coated aluminum foil current collector.

[0011] In a more optimized manner, the upper coating slurry and the lower coating slurry comprise the following components, by weight: 10-60 parts binder, 10-30 parts deionized water, 10-30 parts conductive agent, and 0.1-2 parts curing agent.

[0012] In a more optimized manner, the binder in the undercoat slurry is a styrene / acrylate binder, and the conductive agent is a mixture of graphene and carbon powder.

[0013] In a more optimized manner, the binder in the upper coating slurry is any one or more of polytetrafluoroethylene emulsion, styrene-butadiene emulsion, acrylic binder, and polyvinyl acetate binder, and the conductive agent is carbon nanotubes.

[0014] More preferably, the curing agent is any one or more of sodium hydroxide, calcium hydroxide, aziridine, alkoxysilane, and calcium hydroxide.

[0015] In a more optimized manner, the graphene is modified by means of: taking graphene and toluene, stirring evenly, adding vinyltrimethoxysilane and 2-hydroxy-2-methyl-1-phenyl-1-propanone, reacting for 6-7 hours, filtering and drying to obtain modified graphene.

[0016] More preferably, the binder in the lower coating slurry is a modified acrylic binder. The preparation method of the modified acrylic binder is as follows: take acrylic acid, add deionized water, stir evenly to obtain an acrylic solution, slowly add lithium hydroxide, stir evenly, introduce nitrogen gas, maintain for 10-15 min, raise the temperature to 70-75℃, add vinyltriethoxysilane, continue stirring for 5-10 min, add ammonium persulfate, keep warm for 1-2 h, and obtain the modified acrylic binder.

[0017] In a more optimized manner, the carbon nanotubes are modified by means of the following method: taking carbon nanotubes and N,N-dimethylformamide, stirring for 20-30 min, adding epichlorohydrin, continuing to stir for 1-2 h, adding thiolated chitosan, stirring for 30-40 min, centrifuging, washing, drying, and grinding to obtain modified carbon nanotube powder.

[0018] A more optimized method for preparing the thiolated chitosan includes the following steps:

[0019] S1: Take chitosan and acetic acid, stir them evenly to obtain a chitosan solution; spray the chitosan solution into sodium hydroxide solution, stir for 20-40 min, let stand for 14-18 h, filter and wash to obtain chitosan gel.

[0020] S2: Add chitosan gel to glutaraldehyde solution, stir evenly, let stand for 46-50 h, wash to obtain cross-linked chitosan; add cross-linked chitosan to L-cysteine ​​solution, stir evenly, shake for 24-26 h, wash and dry to obtain thiolated chitosan.

[0021] In a more optimized manner, the following steps are included:

[0022] Step 1: Take modified acrylic adhesive, deionized water, modified graphene powder, carbon powder, and curing agent, stir evenly to obtain the lower coating slurry;

[0023] Step 2: Apply the lower coating slurry to one side of the aluminum foil and bake at 70-130℃ for 20s-3min to obtain the carbon-coated aluminum foil current collector semi-finished product;

[0024] Step 3: Take the adhesive, deionized water, modified carbon nanotubes, and curing agent, stir them evenly to prepare the top coating slurry;

[0025] Step 4: Apply the top coating slurry to the side of the carbon-coated aluminum foil current collector semi-finished product that has the bottom coating slurry, cure it under ultraviolet light for 30-40 minutes, and bake it at 70-130℃ for 20 seconds to 3 minutes to obtain the carbon-coated aluminum foil current collector.

[0026] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0027] (1) This invention improves the coating structure by modifying the binder, thereby enhancing the cohesiveness of the slurry and its contact with the aluminum foil surface. This effectively addresses the volume changes caused by lithium ion deintercalation and intercalation at high and low temperatures, ensuring the stability of the electrode material during charging and discharging. Furthermore, this invention utilizes nano-coating technology to perform single-sided, double-layer heterogeneous coating on the aluminum foil surface. While maintaining the adhesion of the aluminum foil surface, it provides numerous contact sites, enabling a tighter bond between the electrode and the foil during coating, increasing electrode peel strength, improving capacity retention, and ultimately enhancing battery performance.

[0028] (2) This invention uses acrylic acid and vinyltriethoxysilane to prepare a vinyl-modified acrylic adhesive. Modifying graphene with vinyltrimethoxysilane results in the grafting of vinyl groups onto the graphene. These vinyl groups on the graphene can react with the vinyl groups in the modified acrylic adhesive, improving the compatibility of graphene in the undercoating slurry and making it easier to disperse. This further enhances the peel strength and capacity retention of the carbon-coated aluminum foil current collector.

[0029] This invention uses an L-cysteine ​​solution to further treat cross-linked chitosan. The amino groups on the L-cysteine ​​solution can undergo a Schiff base reaction with the aldehyde groups on the cross-linked chitosan, allowing the thiol groups in the L-cysteine ​​to be grafted onto the cross-linked chitosan. Thiol-modified chitosan is then used to modify carbon nanotubes, grafting thiol groups onto the carbon nanotubes.

[0030] This invention uses a modified acrylic binder, modified graphene powder, and carbon powder to prepare a lower coating slurry; and uses a binder and modified carbon nanotubes to prepare an upper coating slurry; then, through ultraviolet curing, the vinyl groups on the modified graphene in the lower coating can react with the thiol groups on the carbon nanotubes in the upper coating, thereby enhancing the peel strength of the coating. Detailed Implementation

[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] There are no special restrictions on the suppliers of any of the raw materials involved in this invention. Exemplary examples include: graphene powder: available from Kramar Reagent, particle size: 5-10 μm; carbon powder: available from Brofos, particle size: 500 nm, catalog number: Brofos-C-500; aluminum sheet: catalog number lp123tt, available from Flextronics Insulation Materials; carbon nanotubes: available from Merck, model: 698849; acrylic binder: available from Merck, catalog number: 278386; styrene / acrylate binder: available from BASF, catalog number: 7066.

[0033] Example 1: A method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries, comprising the following steps:

[0034] Step 1: Take 1 kg of graphene powder and 2 kg of deionized water, and disperse them by ultrasonication to obtain a graphene powder solution; take 8 kg of styrene / acrylate binder, 2 kg of deionized water, 1 kg of carbon powder, 3 kg of graphene powder solution, and 0.02 kg of calcium hydroxide, mix and stir at a stirring speed of 30 rpm for 2.5 h to obtain the lower coating slurry.

[0035] The lower coating slurry is coated onto one side of an aluminum foil with a thickness of 13 μm using a gravure coating method, and then baked at 100°C for 1.5 min to obtain a carbon-coated aluminum foil current collector semi-finished product with a total thickness of 13.5 μm.

[0036] Step 2: Take 1 kg of carbon nanotubes and 2 kg of deionized water, and disperse them by ultrasonication to obtain a carbon nanotube solution; take 8 kg of acrylic adhesive, 2 kg of deionized water, and 3 kg of carbon nanotube solution, mix and stir at a stirring speed of 30 rpm for 2.5 h to obtain the top coating slurry;

[0037] A 0.5 μm top coating slurry is applied to the side of the carbon-coated aluminum foil current collector semi-finished product that has been coated with the bottom coating slurry, and then baked at 100°C for 1.5 min to obtain the carbon-coated aluminum foil current collector.

[0038] Example 2: A method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries, comprising the following steps:

[0039] Step 1: Preparation of thiolated chitosan:

[0040] Take 2g of chitosan and 80mL of 5% acetic acid, stir well to obtain a chitosan solution; spray the chitosan solution into a 0.5mol / L sodium hydroxide solution, stir for 30min, let stand for 16h, filter and wash to obtain chitosan gel.

[0041] Add 3g of chitosan gel to 5mL of 3% glutaraldehyde solution, stir well, let stand for 48h, wash, and obtain cross-linked chitosan; add 3g of cross-linked chitosan to 5mL of 1.5% L-cysteine ​​solution, stir well, shake for 25h, wash and dry, and obtain thiolated chitosan.

[0042] Step 2: Preparation of modified carbon nanotube powder:

[0043] Take 0.1g of carbon nanotube powder and 100mL of N,N-dimethylformamide, stir for 25min, add 2g of epichlorohydrin, continue stirring for 1.5h, add 5g of thiolated chitosan, stir for 35min, centrifuge, wash, dry and grind to obtain modified carbon nanotube powder.

[0044] Step 3: Preparation of modified graphene:

[0045] Take 0.1g of graphene and 200mL of toluene, stir well, add 0.85mL of vinyltrimethoxysilane and 0.1mL of 2-hydroxy-2-methyl-1-phenyl-1-propanone, react for 6h, filter and dry to obtain modified graphene powder.

[0046] Step 4: Preparation of modified acrylic adhesive:

[0047] The molar ratio of vinyltriethoxysilane, acrylic acid, lithium hydroxide, and ammonium persulfate is 0.07:1:1:1;

[0048] Acrylic acid was added to deionized water and stirred until homogeneous to obtain an acrylic acid solution with a solid content of 20%. Lithium hydroxide was slowly added and stirred until homogeneous. Nitrogen gas was introduced and maintained for 12 minutes. The temperature was raised to 72°C, vinyltriethoxysilane was added, and stirring was continued for 8 minutes. Ammonium persulfate was added and the temperature was maintained for 1.5 hours to obtain a modified acrylic adhesive.

[0049] Step 5: Take 1 kg of modified graphene powder and 2 kg of deionized water, and disperse them by ultrasonication to obtain a modified graphene powder solution; take 8 kg of modified acrylic binder, 2 kg of deionized water, 1 kg of carbon powder, 3 kg of modified graphene powder solution, and 0.02 kg of calcium hydroxide and mix them at a stirring speed of 30 rpm for 2.5 h to obtain the lower slurry.

[0050] The lower layer of slurry is coated onto one side of an aluminum foil with a thickness of 13 μm using a gravure coating method, and then baked at 75°C for 40 seconds to obtain a carbon-coated aluminum foil current collector semi-finished product with a total thickness of 13.5 μm.

[0051] Step 6: Take 1 kg of modified carbon nanotubes and 2 kg of deionized water, and disperse them by ultrasonication to obtain a modified carbon nanotube solution; take 8 kg of acrylic binder, 2 kg of deionized water, and 3 kg of modified carbon nanotube solution, mix and stir at a stirring speed of 30 rpm for 2.5 h to obtain the upper slurry;

[0052] A 0.5µm layer of top slurry is coated on the side of the carbon-coated aluminum foil current collector semi-finished product that is coated with the bottom slurry. The product is then light-cured under an 800W UV lamp for 35 minutes and baked at 110℃ for 2 minutes to obtain the carbon-coated aluminum foil current collector.

[0053] Example 3: A method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries, comprising the following steps:

[0054] Step 1: Preparation of thiolated chitosan:

[0055] Take 2g of chitosan and 80mL of 5% acetic acid, stir well to obtain a chitosan solution; spray the chitosan solution into a 0.5mol / L sodium hydroxide solution, stir for 20min, let stand for 18h, filter and wash to obtain chitosan gel;

[0056] Add 3g of chitosan gel to 5mL of 3% glutaraldehyde solution, stir well, let stand for 46h, wash, and obtain cross-linked chitosan; add 3g of cross-linked chitosan to 5mL of 1.5% L-cysteine ​​solution, stir well, shake for 24h, wash and dry, and obtain thiolated chitosan.

[0057] Step 2: Preparation of modified carbon nanotube powder:

[0058] Take 0.1g of carbon nanotube powder and 100mL of N,N-dimethylformamide, stir for 20min, add 2g of epichlorohydrin, continue stirring for 1h, add 5g of thiolated chitosan, stir for 30min, centrifuge, wash, dry and grind to obtain modified carbon nanotube powder.

[0059] Step 3: Preparation of modified graphene:

[0060] Take 0.1g of graphene and 200mL of toluene, stir well, add 0.85mL of vinyltrimethoxysilane and 0.1mL of 2-hydroxy-2-methyl-1-phenyl-1-propanone, react for 6h, filter and dry to obtain modified graphene powder.

[0061] Step 4: Preparation of modified acrylic adhesive:

[0062] The molar ratio of vinyltriethoxysilane, acrylic acid, lithium hydroxide, and ammonium persulfate is 0.07:1:1:1;

[0063] Acrylic acid was added to deionized water and stirred until homogeneous to obtain an acrylic acid solution with a solid content of 20%. Lithium hydroxide was slowly added and stirred until homogeneous. Nitrogen gas was introduced and maintained for 10 minutes. The temperature was raised to 70°C, vinyltriethoxysilane was added, and stirring was continued for 5 minutes. Ammonium persulfate was added and the temperature was maintained for 1 hour to obtain a modified acrylic adhesive.

[0064] Step 5: Take 1 kg of modified graphene powder and 2 kg of deionized water, and disperse them by ultrasonication to obtain a modified graphene powder solution; take 8 kg of modified acrylic binder, 2 kg of deionized water, 1 kg of carbon powder, 3 kg of modified graphene powder solution, and 0.02 kg of calcium hydroxide and mix them at a stirring speed of 10 rpm for 2 hours to obtain the lower slurry.

[0065] The lower layer of slurry is coated onto one side of an aluminum foil with a thickness of 13 μm using a gravure coating method, and then baked at 70°C for 50 seconds to obtain a carbon-coated aluminum foil current collector semi-finished product with a total thickness of 13.5 μm.

[0066] Step 6: Take 1 kg of modified carbon nanotubes and 2 kg of deionized water, and disperse them by ultrasonication to obtain a modified carbon nanotube solution; take 8 kg of acrylic binder, 2 kg of deionized water, and 3 kg of modified carbon nanotube solution, mix and stir at a stirring speed of 30 rpm for 2 hours to obtain the upper slurry;

[0067] A 0.5µm layer of top slurry is coated on the side of the carbon-coated aluminum foil current collector semi-finished product that has a lower slurry coating. The product is then light-cured under an 800W UV lamp for 30 minutes and baked at 120℃ for 3 minutes to obtain the carbon-coated aluminum foil current collector.

[0068] Example 4: A method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries, comprising the following steps:

[0069] Step 1: Preparation of thiolated chitosan:

[0070] Take 2g of chitosan and 80mL of 5% acetic acid, stir well to obtain a chitosan solution; spray the chitosan solution into a 0.5mol / L sodium hydroxide solution, stir for 40min, let stand for 18h, filter and wash to obtain chitosan gel;

[0071] Add 3g of chitosan gel to 5mL of 3% glutaraldehyde solution, stir well, let stand for 50h, wash, and obtain cross-linked chitosan; add 3g of cross-linked chitosan to 5mL of 1.5% L-cysteine ​​solution, stir well, shake for 26h, wash and dry, and obtain thiolated chitosan.

[0072] Step 2: Preparation of modified carbon nanotube powder:

[0073] Take 0.1g of carbon nanotube powder and 100mL of N,N-dimethylformamide, stir for 30min, add 2g of epichlorohydrin, continue stirring for 2h, add 5g of thiolated chitosan, stir for 40min, centrifuge, wash, dry and grind to obtain modified carbon nanotube powder.

[0074] Step 3: Preparation of modified graphene:

[0075] Take 0.1g of graphene and 200mL of toluene, stir well, add 0.85mL of vinyltrimethoxysilane and 0.1mL of 2-hydroxy-2-methyl-1-phenyl-1-propanone, react for 6h, filter and dry to obtain modified graphene powder.

[0076] Step 4: Preparation of modified acrylic adhesive:

[0077] The molar ratio of vinyltriethoxysilane, acrylic acid, lithium hydroxide, and ammonium persulfate is 0.07:1:1:1;

[0078] Acrylic acid was added to deionized water and stirred until homogeneous to obtain an acrylic acid solution with a solid content of 20%. Lithium hydroxide was slowly added and stirred until homogeneous. Nitrogen gas was introduced and maintained for 15 minutes. The temperature was raised to 75°C, vinyltriethoxysilane was added, and stirring was continued for 10 minutes. Ammonium persulfate was added and the temperature was maintained for 2 hours to obtain a modified acrylic adhesive.

[0079] Step 5: Take 1 kg of modified graphene powder and 2 kg of deionized water, and disperse them by ultrasonication to obtain a modified graphene powder solution; take 8 kg of modified acrylic binder, 2 kg of deionized water, 1 kg of carbon powder, 3 kg of modified graphene powder solution, and 0.02 kg of calcium hydroxide and mix them at a stirring speed of 40 rpm for 3 hours to obtain the lower slurry.

[0080] The lower layer of slurry is coated onto one side of an aluminum foil with a thickness of 13 μm using a gravure coating method, and then baked at 80°C for 20 seconds to obtain a carbon-coated aluminum foil current collector semi-finished product with a total thickness of 13.5 μm.

[0081] Step 6: Take 1 kg of modified carbon nanotubes and 2 kg of deionized water, and disperse them by ultrasonication to obtain a modified carbon nanotube solution; take 8 kg of acrylic binder, 2 kg of deionized water, and 3 kg of modified carbon nanotube solution, mix and stir at a stirring speed of 40 rpm for 2 hours to obtain the upper slurry;

[0082] A 0.5µm layer of top slurry is coated on the side of the carbon-coated aluminum foil current collector semi-finished product that is coated with the bottom slurry. The product is then light-cured under an 800W UV lamp for 40 minutes and baked at 130℃ for 1 minute to obtain the carbon-coated aluminum foil current collector.

[0083] Comparative Example 1:

[0084] Step 1: Take 1 kg of graphene powder, 1 kg of carbon nanotubes and 4 kg of deionized water, and disperse them by ultrasonication to obtain a conductive powder solution; take 16 kg of styrene / acrylate binder, 4 kg of deionized water, 1 kg of carbon powder, conductive powder solution and 0.04 kg of calcium hydroxide and mix them at a stirring speed of 30 rpm for 2.5 h to obtain a coating slurry.

[0085] The coating slurry was applied to one side of an aluminum foil with a thickness of 13 μm using a gravure coating method, and then baked at 100°C for 1.5 min to obtain a carbon-coated aluminum foil current collector with a total thickness of 14 μm.

[0086] Comparative Example 2: Graphene was not modified using vinyltrimethoxysilane; all other aspects were the same as in Example 2.

[0087] Step 1: Preparation of thiolated chitosan:

[0088] Take 2g of chitosan and 80mL of 5% acetic acid, stir well to obtain a chitosan solution; spray the chitosan solution into a 0.5mol / L sodium hydroxide solution, stir for 30min, let stand for 16h, filter and wash to obtain chitosan gel.

[0089] Add 3g of chitosan gel to 5mL of 3% glutaraldehyde solution, stir well, let stand for 48h, wash, and obtain cross-linked chitosan; add 3g of cross-linked chitosan to 5mL of 1.5% L-cysteine ​​solution, stir well, shake for 25h, wash and dry, and obtain thiolated chitosan.

[0090] Step 2: Preparation of modified carbon nanotube powder:

[0091] Take 0.1g of carbon nanotube powder and 100mL of N,N-dimethylformamide, stir for 25min, add 2g of epichlorohydrin, continue stirring for 1.5h, add 5g of thiolated chitosan, stir for 35min, centrifuge, wash, dry and grind to obtain modified carbon nanotube powder.

[0092] Step 3: Preparation of modified acrylic adhesive:

[0093] The molar ratio of vinyltriethoxysilane, acrylic acid, lithium hydroxide, and ammonium persulfate is 0.07:1:1:1;

[0094] Acrylic acid was added to deionized water and stirred until homogeneous to obtain an acrylic acid solution with a solid content of 20%. Lithium hydroxide was slowly added and stirred until homogeneous. Nitrogen gas was introduced and maintained for 12 minutes. The temperature was raised to 72°C, vinyltriethoxysilane was added, and stirring was continued for 8 minutes. Ammonium persulfate was added and the temperature was maintained for 1.5 hours to obtain a modified acrylic adhesive.

[0095] Step 4: Take 1 kg of graphene powder and 2 kg of deionized water, and disperse them by ultrasonication to obtain a graphene powder solution; take 8 kg of modified acrylic binder, 2 kg of deionized water, 1 kg of carbon powder, 3 kg of graphene powder solution, and 0.02 kg of calcium hydroxide and mix them. The mixing speed is 30 rpm and the mixing time is 2.5 h to obtain the lower slurry.

[0096] The lower layer of slurry is coated onto one side of an aluminum foil with a thickness of 13 μm using a gravure coating method, and then baked at 75°C for 40 seconds to obtain a carbon-coated aluminum foil current collector semi-finished product with a total thickness of 13.5 μm.

[0097] Step 5: Take 1 kg of modified carbon nanotubes and 2 kg of deionized water, and disperse them by ultrasonication to obtain a modified carbon nanotube solution; take 8 kg of acrylic binder, 2 kg of deionized water, and 3 kg of modified carbon nanotube solution, mix and stir at a stirring speed of 30 rpm for 2.5 h to obtain the upper slurry.

[0098] A 0.5µm layer of top slurry is coated on the side of the carbon-coated aluminum foil current collector semi-finished product that is coated with the bottom slurry. The product is then light-cured under an 800W UV lamp for 35 minutes and baked at 110℃ for 2 minutes to obtain the carbon-coated aluminum foil current collector.

[0099] Comparative Example 3: Carbon nanotubes were modified without the use of thiolated chitosan; all other aspects were the same as in Example 2.

[0100] Step 1: Preparation of modified graphene:

[0101] Take 0.1g of graphene and 200mL of toluene, stir well, add 0.85mL of vinyltrimethoxysilane and 0.1mL of 2-hydroxy-2-methyl-1-phenyl-1-propanone, react for 6h, filter and dry to obtain modified graphene powder.

[0102] Step 2: Preparation of modified acrylic adhesive:

[0103] The molar ratio of vinyltriethoxysilane, acrylic acid, lithium hydroxide, and ammonium persulfate is 0.07:1:1:1;

[0104] Acrylic acid was added to deionized water and stirred until homogeneous to obtain an acrylic acid solution with a solid content of 20%. Lithium hydroxide was slowly added and stirred until homogeneous. Nitrogen gas was introduced and maintained for 12 minutes. The temperature was raised to 72°C, vinyltriethoxysilane was added, and stirring was continued for 8 minutes. Ammonium persulfate was added and the temperature was maintained for 1.5 hours to obtain a modified acrylic adhesive.

[0105] Step 3: Take 1 kg of modified graphene powder and 2 kg of deionized water, and disperse them by ultrasonication to obtain a modified graphene powder solution; take 8 kg of modified acrylic binder, 2 kg of deionized water, 1 kg of carbon powder, 3 kg of modified graphene powder solution, and 0.02 kg of calcium hydroxide and mix them at a stirring speed of 30 rpm for 2.5 h to obtain the lower slurry.

[0106] The lower layer of slurry is coated onto one side of an aluminum foil with a thickness of 13 μm using a gravure coating method, and then baked at 75°C for 40 seconds to obtain a carbon-coated aluminum foil current collector semi-finished product with a total thickness of 13.5 μm.

[0107] Step 4: Take 1 kg of modified carbon nanotubes and 2 kg of deionized water, and disperse them by ultrasonication to obtain a modified carbon nanotube solution; take 8 kg of acrylic binder, 2 kg of deionized water, and 3 kg of modified carbon nanotube solution, mix and stir at a stirring speed of 30 rpm for 2.5 h to obtain the upper slurry;

[0108] A 0.5µm layer of top slurry is applied to the side of the carbon-coated aluminum foil current collector semi-finished product that is coated with the bottom slurry. The product is then light-cured under an 800W UV lamp for 35 minutes and baked at 110℃ for 2 minutes to obtain the carbon-coated aluminum foil current collector.

[0109] experiment:

[0110] The performance of carbon-coated aluminum foil current collectors prepared in Examples 1-4 and Comparative Examples 1-3 was tested. The carbon-coated aluminum foil current collectors were cut into samples with a length of 12 cm and a width of 5 cm using a peel strength tester, and the peel strength of the samples was tested. The carbon-coated aluminum foil was used to make batteries, which were charged at a constant current rate to 3.65V, then charged at a constant voltage with a cutoff current of 0.05C. The batteries were then left to stand for 15 minutes at different ambient temperatures, and then discharged at the same rate to 2.5V with a current range of 5-30A. The charge-discharge capacity retention rate at different temperatures was tested, and the data are shown in the table below.

[0111] Example 1 750 92.32% 94.52% Example 2 812 93.72% 96.28% Example 3 810 93.70% 96.26% Example 4 813 93.73% 96.32% Comparative Example 1 485 78.54% 91.23% Comparative Example 2 787 92.83% 95.12% Comparative Example 3 795 93.21% 95.84%

[0112] Conclusion: The data comparison in the table shows that in Comparative Example 1, where the coating slurry was applied to one side of the aluminum foil, the bond between the slurry and the foil in the prepared carbon-coated aluminum foil current collector was not strong enough, with a peel strength of only 485 N·m. -1 The capacity retention rate also decreased significantly. In Comparative Example 2, without using vinyltrimethoxysilane to modify graphene, the graphene dispersion in the lower coating slurry was poor, resulting in a decrease in peel strength and capacity retention rate. In Comparative Example 3, without using thiolated chitosan to modify carbon nanotubes, the modified graphene in the lower coating could not react with the carbon nanotubes in the upper coating, leading to a decrease in the performance of the carbon-coated aluminum foil current collector. The peel strength of the carbon-coated aluminum foil current collector prepared by this invention can reach 810 N·m. -1 The capacity retention rate can reach 93% at -10℃ and 96% at 30℃. This invention coats the current collector with two layers of slurry, improving the slurry's cohesiveness and contact with the aluminum foil surface. This effectively addresses volume changes caused by lithium-ion insertion / extraction at high and low temperatures, ensuring the stability of the electrode material during charge and discharge. While maintaining adhesion to the aluminum foil surface, it provides numerous contact points, allowing for a tighter bond between the electrode coating and the foil, increasing electrode peel strength, improving capacity retention, and ultimately enhancing battery performance.

[0113] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries, characterized in that: Includes the following steps: Step 1: Take the adhesive, deionized water, conductive agent, and curing agent, stir them evenly to obtain the lower coating slurry; Step 2: Apply the lower coating slurry to one side of the aluminum foil and bake at 70-130℃ for 20s-3min to obtain the carbon-coated aluminum foil current collector semi-finished product; Step 3: Take the adhesive, deionized water, conductive agent, and curing agent, stir them evenly to prepare the top coating slurry; Step 4: Apply the top coating slurry to the side of the carbon-coated aluminum foil current collector semi-finished product that has the bottom coating slurry, and bake it at 70-130℃ for 20s-3min to obtain the carbon-coated aluminum foil current collector. The binder in the undercoat slurry is a modified acrylic binder, and the conductive agent is a mixture of graphene and carbon powder; The curing agent is any one or more of sodium hydroxide, calcium hydroxide, aziridine, alkoxysilane, and calcium hydroxide; The graphene was modified by means of the following method: taking graphene and toluene, stirring evenly, adding vinyltrimethoxysilane and 2-hydroxy-2-methyl-1-phenyl-1-propanone, reacting for 6-7 hours, filtering and drying to obtain modified graphene. The modified acrylic adhesive is prepared as follows: take acrylic acid, add deionized water, stir evenly to obtain an acrylic acid solution, slowly add lithium hydroxide, stir evenly, introduce nitrogen gas, maintain for 10-15 min, heat to 70-75℃, add vinyltriethoxysilane, continue stirring for 5-10 min, add ammonium persulfate, keep warm for 1-2 h, and obtain the modified acrylic adhesive.

2. The method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries according to claim 1, characterized in that: The upper coating slurry and the lower coating slurry comprise the following components, by weight: 10-60 parts binder, 10-30 parts deionized water, 10-30 parts conductive agent, and 0.1-2 parts curing agent.

3. The method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries according to claim 1, characterized in that: The binder in the top coating slurry is any one or more of polytetrafluoroethylene emulsion, styrene-butadiene emulsion, acrylic binder, and polyvinyl acetate binder, and the conductive agent is carbon nanotubes.

4. The method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries according to claim 3, characterized in that: The carbon nanotubes were modified by means of the following method: taking carbon nanotubes and N,N-dimethylformamide, stirring for 20-30 min, adding epichlorohydrin, continuing to stir for 1-2 h, adding thiolated chitosan, stirring for 30-40 min, centrifuging, washing, drying, and grinding to obtain modified carbon nanotube powder.

5. The method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries according to claim 4, characterized in that: The method for preparing the thiolized chitosan is as follows: Includes the following steps: S1: Take chitosan and acetic acid, stir them evenly to obtain a chitosan solution; spray the chitosan solution into sodium hydroxide solution, stir for 20-40 min, let stand for 14-18 h, filter and wash to obtain chitosan gel. S2: Add chitosan gel to glutaraldehyde solution, stir evenly, let stand for 46-50 h, wash to obtain cross-linked chitosan; add cross-linked chitosan to L-cysteine ​​solution, stir evenly, shake for 24-26 h, wash and dry to obtain thiolated chitosan.

6. A method for preparing a high-strength carbon-coated aluminum foil current collector for lithium batteries according to any one of claims 1-5, characterized in that: Includes the following steps: Step 1: Take modified acrylic adhesive, deionized water, modified graphene powder, carbon powder, and curing agent, stir evenly to obtain the lower coating slurry; Step 2: Apply the lower coating slurry to one side of the aluminum foil and bake at 70-130℃ for 20s-3min to obtain the carbon-coated aluminum foil current collector semi-finished product; Step 3: Take the adhesive, deionized water, modified carbon nanotubes, and curing agent, stir them evenly to prepare the top coating slurry; Step 4: Apply the top coating slurry to the side of the carbon-coated aluminum foil current collector semi-finished product that has the bottom coating slurry, cure it under ultraviolet light for 30-40 minutes, and bake it at 70-130℃ for 20 seconds to 3 minutes to obtain the carbon-coated aluminum foil current collector.

Citation Information

Patent Citations

  • Carbon-coated aluminum foil, preparation method and application

    CN106602076A

  • Negative electrode sheet and method for preparing the same, secondary battery, battery module, battery pack, and electrical apparatus

    US20230291043A1